2012
DOI: 10.1128/jvi.05167-11
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus Latency-Associated Nuclear Antigen Induction by Hypoxia and Hypoxia-Inducible Factors

Abstract: Hypoxia and hypoxia-inducible factors (HIFs) play an important role in the Kaposi's sarcoma-associated herpesvirus (KSHV) life cycle. In particular, hypoxia can activate lytic replication of KSHV and specific lytic genes, including the replication and transcription activator (RTA), while KSHV infection in turn can increase the levels and activity of HIFs. In the present study, we show that hypoxia increases the levels of mRNAs encoding KSHV latency-associated nuclear antigen (LANA) in primary effusion lymphoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 54 publications
2
36
1
Order By: Relevance
“…As HIF-1␣ functionally and physically associates with KDM3A (34,62), it is possible that LANA, HIF-1␣, and KDM3A can form a ternary complex under hypoxic conditions. In accord with this, the KDM3A recruitment sites that we identified significantly overlap HIF-1␣ binding sites (63).…”
Section: Discussionsupporting
confidence: 60%
“…As HIF-1␣ functionally and physically associates with KDM3A (34,62), it is possible that LANA, HIF-1␣, and KDM3A can form a ternary complex under hypoxic conditions. In accord with this, the KDM3A recruitment sites that we identified significantly overlap HIF-1␣ binding sites (63).…”
Section: Discussionsupporting
confidence: 60%
“…tent with a recent report showing that hypoxia enhanced LANA expression (43). In addition, the role of KAP1 in response to extracellular stress like hypoxia or TPA-NaB treatment is not unique.…”
Section: Discussionsupporting
confidence: 60%
“…However, it is not fully understood how hypoxia induces reactivation from KSHV latency. To address this question, we and other groups have found that hypoxia not only induces the key latent antigen LANA encoded by KSHV but also cooperates with HIF-1␣ bound to HREs within the RTA promoter (10,43) to directly induce lytic gene expression (i.e., ORF34-37) for lytic replication (44). Interestingly, we and other groups have found that HIF-1␣ is stabilized and accumulated in both PEL and KS cells in normoxia (29,36).…”
Section: Discussionmentioning
confidence: 99%
“…Several inducers of RTA expression have been reported in PEL cell lines. Hypoxia induces RTA expression through the hypoxia-inducible factor-1α pathway in vitro [10]. RTA is also induced by the unfolded protein response, endoplasmic reticulum stress 11], unspliced X-box-binding protein 1 [12], Toll-like receptor 7 and 8 activation, and Ras signaling (Raf/MEK/ERK/Ets-1 pathways) [13].…”
Section: Introductionmentioning
confidence: 99%